Association of paternal IQ in early adulthood with offspring mortality and hospital admissions for injuries: a cohort study of 503 492 Swedish children. Issue 7 (17th April 2014) - Jelenkovic, Aline; Silventoinen, Karri; Tynelius, Per; Rasmussen, Finn
Abstract : Background: Higher intelligence (IQ) has been related to a lower risk of mortality and hospital admissions for injuries, but little is known about the effect of parental IQ on offspring outcomes. We explored associations of paternal IQ with mortality and hospitalisations for injuries from all external causes in offspring. Methods: A cohort of 503 492 Swedish children under 5 years of age with information on paternal IQ was obtained by record linkage of national registers. HR with 95% CIs were estimated using Cox regression. Results: There was some evidence that paternal IQ was inversely associated with total and external-cause mortality in offspring, although the effects were modest and disappeared when controlling for parents' socioeconomic position (SEP). The only robust gradient was found between paternal IQ and hospital admissions for injuries (HRper 1-SD increase in IQ 0.93, 95% CI 0.92 to 0.94; p<0.001), which was slightly attenuated but retained statistical significance after adjustment for SEP (0.95, 95% CI 0.94 to 0.97; p<0.001). Conclusions: Children to fathers with lower IQ may have an increased risk of injury by external causes. Messages on family safety and injury prevention might be tailored according to parental cognitive abilities.